Effects of M-health Intervention on Physical Activity Status in Older Adults with Type 2 Diabetes: Using Health Action Process Approach Model - Fatemeh Zanjanchi Neko; Isa Mohammadi Zeidi; Hadi Morshedi; Banafsheh Mohammadi Zeidi (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: Providing mobile-based cognitive-behavioral interventions reduces physical complications and enhances the quality of life in diabetic patients by improving physical activities. The present study aimed to determine the effect of a model-based intervention based on the health action process approach model (HAPA) on physical activity in the elderly with type 2 diabetes in Qazvin. Methods: The current study was a randomized controlled trial, and using a simple random sampling method, 120 elderly people with type 2 diabetes participated in experimental and control groups. The educational intervention consisted of six virtual training sessions with the aim of promoting the psychological constructs affecting physical activity through short lectures, group discussions, and individual counseling associated with educational pamphlets, audio files, and educational SMS. The scales related to the HAPA model and international physical activity questionnaire (IPAQs) were completed by two groups before and three months after the educational intervention. The data were analyzed in SPSS software (version 25.0), and a significance level of less than 0.05 was considered. Results: The mean age of the participants was 60.7 ± 9.23 years, and 64.17% of cases were female. The results of covariance analysis demonstrated that by controlling the effect of the pre-test, the mean of HAPA constructs as perceived risk, outcome expectancy, social support, action self-efficacy, maintenance self-efficacy, recovery self-efficacy, action planning, coping planning, behavioral intention, and the level of physical activity improved in the experimental group (P<0.001). Conclusion: As evidenced by the obtained results, the provision of mobile-based cognitive-behavioral interventions led to an increase in the level of physical activity in diabetic patients by improving the psychological variables related to the HAPA model.